UPAYA MENINGKATKAN KARAKTER KEPEMIMPINAN MELALUI PEMBELAJARAN SEJARAH KISAH KERTARAJASA JAYAWARDHANA - Latifah Latifah (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
The name Kertarajasa College of Buddhism (STAB) was taken from the first king of the Majapahit Kingdom, namely Kertarajasa Jayawardana. It is hoped that the use of Kertarajasa’s name will enable STAB academics to emulate his leadership character. However, this name will lose its meaning if the younger generation, especially students, does not know and understand who he is. Therefore, this study aims to develop a character learning strategy through the example of a historical figure, Kertarajasa Jayawardhana, in a special workshop for STAB students. The research method used is a quasi-experimental method, using pre-test and post-test as a form of value internalization. Students who are research subjects directly experience the workshop activities (experiential learning). They were asked to confirm the values they learned from the character Kertarajasa Jayawardhana by self-reflection on nature and cooperative learning. Based on the pre-test and post-test scores, the study results did not show a significant difference in the character of STAB Kertarajasa students. There are values from Kertarajasa Jayawardhana's leadership that have inspired students to imitate him, for example: becoming a progressive leader. However, some matters are owned by the character but have not been able to be captured by students, and the only one is the visionary character.